Cancer as a Proinflammatory Environment: Metastasis and Cachexia - Nelson Inácio Pinto; June Carnier; Lila M. Oyama; Jose Pinhata Otoch; Paulo Sergio Alcântara; Flavio Tokeshi; Claudia M. Nascimento (Hindawi Limited, 2015)
The development of the syndrome of cancer cachexia and that of metastasis are related with a poor prognostic for cancer patients. They are considered multifactorial processes associated with a proinflammatory environment, to which tumour microenvironment and other tissues from the tumour bearing individuals contribute. The aim of the present review is to address the role of ghrelin, myostatin, leptin, HIF, IL-6, TNF-α, and ANGPTL-4 in the regulation of energy balance, tumour development, and tumoural cell invasion. Hypoxia induced factor plays a prominent role in tumour macro- and microenvironment, by modulating the release of proinflammatory cytokines.